NILAI-NILAI ETIKA DALAM CERITA UDYOGA PARWA - Made Urip Dharmaputra (JAPAM (Jurnal Pendidikan Agama), 2024)
The aim of writing this article is to interpret the ethical values in the Udyoga Parwa story. The method used in this research is descriptive qualitative with an interpretive analysis model. This type of research is classified as library research with a humanities study based on a hermeneutical approach. Udyoga Parwa is the fifth series of Asta Daśa Parwa which consists of 10 sub-sections. Etymologically, Udyoga means effort or effort. Udyoga Parwa as a whole tells about the end of the Pāṇḍawa exile and peace efforts to prevent civil war. Talking about peace diplomacy efforts, Udyoga Parwa gave his views regarding the importance of the role of a dūta in carrying out conciliation and the role of a king in building alliances with other kings to anticipate any possibility of war. Descriptions of the theory of peace and diplomacy are also contained in each Udyoga Parwa story which is the inspiration for other śāstra works such as Arthaśāstra or Nītiśāstra. In this case, politics is positioned as an effort to solve problems and resolve conflicts. Politics in the story Udyoga Parwa actually emphasizes Dharma which functions to regulate human life. Even though politics in Hindu philosophy is built to organize the system of life, in fact there are still those who think that politics is dirty and is always synonymous with war or the struggle for power. The philosophy of ethical teachings in the Udyoga Parwa story ultimately also provides a narrative about the accountability of human moral obligations in every aspect of life.